A partial quantitative chemical analysis of Pila luzonica - Abantas, Shalem Al.; Lagunay, Dennis S.; De los Reyes, Cesar (Tacloban City Shalem Al. Abantas [and] Dennis S. Lagunay, 1986)
This study dealt with the partial quantitative chemical analysis of Pila luzonica. Specifically, this study obtained the crude content (moisture, ash, protein, and lipids) of the edible snail through standard chemical procedures and determined the percentage composition of each component. The edible snail Pila luzonica, had on the average 31.66% moisture, 21.03% ash, 35.72% protein, and 13.59% lipids. This result is quite significant. The high moisture, ash, protein, and lipid content of the snail's edible meat, could then cater to the necessary nutritional needs of the body. As a consequence, this could then be considered a good food substitute based on the study's findings.
Undergraduate thesis (B.S. in Biological Sciences)--University of the Philippines College Tacloban, March 1986.
Keywords: Snails -- Pila luzonica; Kuhol (Pila luzonica).; Science and Technology